Social Banking: An alternative for unbanked and underbanked - Orunruk, Sorn Sutthikhun (Business Administration and Economics Review, 2023)
Currently, consumers are familiar with technology in the digital age and people spend more time on social media due to the convenience of doing all digital financial transactions in one application, giving them more choices from platforms. Therefore, the social media platform business relies on the bank's strengths in fully digital financial services and the trust that customers have in the bank. In addition, consumers will be more convenient, not having to leave the social platform they are using to go directly to the bank's mobile banking application to perform financial transactions, thus making it easier for consumers to access financial services. Social media platforms extend business models linked to banking services become to “Social Banking” that help people in the country reduce financial transaction costs or borrowing costs. Over the past year, a record number of new accounts have been opened worldwide by firms providing mobile money, fintech, and online banking services. Therefore, the concept of financial inclusion or increasing access to financial services is used to solve the problem of informal debt and inequality without limiting transactions to banks so that people in rural areas can use Social Banking to manage their finances. This article is a study on financial technology known as “Social Banking”, an alternative financial service for the underbanked and unbanked, with the goal of studying trends and patterns of social banking. Social Banking is new, it is necessary to study and understand because it is a financial transaction through social media platforms that are related to security and privacy.